2013
DOI: 10.3109/0167482x.2013.824418
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy beliefs and fear of childbirth in nulliparous women

Abstract: Objective: To explore how childbirth self-efficacy, i.e. outcome expectancy and efficacy expectancy, was associated with fear of childbirth (FOC) and how efficacy expectancy and FOC respectively were related to socio-demographic characteristics, mental problems and preference for a caesarean section. Methods:In this cross sectional study, a consecutive sample of 1000 pregnant nulliparous women was sent the Wijma Delivery Expectancy Questionnaire and Childbirth Self-Efficacy Inventory. Statistical analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
105
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 39 publications
12
105
1
1
Order By: Relevance
“…Our results showed that this applied to only a fraction (3.1%) of all pregnant women (2.2% of nulliparous and 4.0% of parous). This is supported by the strong correlation between a severe FOC and a request for CS as seen in our results (p<0.0001), and is in line with the results in previous studies conducted both in Sweden (Wiklund, Edman, & Andolf 2007;Salomonsson et al 2013) and in a multi-centre study conducted in five European countries (Ryding et al 2015).…”
Section: Generalsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that this applied to only a fraction (3.1%) of all pregnant women (2.2% of nulliparous and 4.0% of parous). This is supported by the strong correlation between a severe FOC and a request for CS as seen in our results (p<0.0001), and is in line with the results in previous studies conducted both in Sweden (Wiklund, Edman, & Andolf 2007;Salomonsson et al 2013) and in a multi-centre study conducted in five European countries (Ryding et al 2015).…”
Section: Generalsupporting
confidence: 93%
“…and for parous 60.7 (SD 24.9). Similar levels have been seen in a mixed Finnish (mean W-DEQ A sum score 68.3) and in a nulliparous Swedish sample (mean W-DEQ A sum score 68.5) (Rouhe et al 2009;Salomonsson, Gullberg, Alehagen & Wijma 2013). Studies in other Western countries have reported lower mean W-DEQ A sum scores in mixed samples (mean W-DEQ A sum score 49.5-57.0) (Toohill, Fenwick, Gamble & Greedy 2014a;Lucasse, Schei & Ryding 2014).…”
Section: Generalsupporting
confidence: 74%
“…It has been associated with factors such as nulliparity (Rouhe, Salmela-Aro, Halmesmaki, & Saisto, 2009), increased gestation (Rouhe et al, 2009), poor mental health (Laursen, Hedegaard, & Johansen, 2008;Storksen, Eberhard-Gran, Garthus-Niegel, & Eskild, 2012), a history of abuse (Lukasse, Vangen, Oian, & Schei, 2011;Nerum, Halvorsen, Sorlie, & Oian, 2006), younger age (Laursen et al, 2008), lower education (Laursen et al, 2008), and low self-efficacy (Salomonsson, Gullberg, Alehagen, & Wijma, 2013). Although fear of childbirth is more common in nulliparous women, women who have a negative or traumatic experience of birth are almost five times more likely to report fear of childbirth in a subsequent pregnancy (Storksen, Garthus-Niegel, Vangen, & Eberhard-Gran, 2013).…”
Section: Fear Of Childbirthmentioning
confidence: 99%
“…[16, 18,19] The factors influencing a woman's degree of satisfaction "have only been studied rudimentarily and are therefore incompletely understood". [20] In particular, we are not aware of any previous investigation conducted in Spain along the lines of the present study.…”
Section: Introductionmentioning
confidence: 99%